Lemon peel oil as an alternative fuel for GDI engines: A spray characterization perspective. (November 2019) - Biswal, Abinash; Kale, Rakesh; Balusamy, Saravanan; Banerjee, Raja; Kolhe, Pankaj
Abstract: Lemon peel oil (LPO: C10 H16 O0.082 ) shows very similar calorific value, stoichiometric air to fuel ratio as isooctane, an ideal reference fuel for a gasoline engine, and also possesses very good anti-knock tendency and octane number rating (RON = 80) making it possible alternative fuel for gasoline engines. The present study investigates the suitability of LPO for direct injection spark ignition application by contrasting the spray characteristics of LPO with reference fuel isooctane for simulated engine-like conditions. Experiments were performed in a constant volume spray chamber under various engine-like pressure and temperature conditions. A six-hole GDI injector was used to study the spray behavior of LPO and then compared to standard reference fuel, isooctane. The ambient conditions in the chamber were derived using the crank resolved pressure data of the GDI engine. The selected chamber conditions are a) 1.5 bar, 329 K; b) 2.5 bar, 371 K; c) 6.0 bar, 453 K simulating in-cylinder conditions for three different injection timings. Phase Doppler particle analyzer and Mie scatter imaging techniques were employed for spray characterization. Spray morphology along with joint probability distribution for droplet size and axial velocity, cumulative volume fraction and Weber and Reynolds number ranges were used to contrast the two sprays for LPO and isooctane. Results showed that ambient pressure and temperature have a significant effect on spray behavior and late injection in compression stroke is proposed to be ideal for LPO to match the engine performance with that of isooctane based on the spray quality comparison. Highlights: Spatio-temporal evolution of Lemon Peel Oil (LPO) with GDI injector is studied. LPO spray is characterized for ambient simulating in-cylinder conditions. Three different injection timings based in-cylinder conditions are explored. Alternate statistical (Joint-PDF; CVF; Re Vs We) description of sprays is proposed. Optimal injection strategy is proposed for LPO utilization in GDI engines.